การยกเลิกความผิดอาญา ศึกษากรณีการผลิตเบียร์เพื่อการบริโภคโดยไม่มีใบอนุญาต - จิรายุ เสรีอภินันท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The objective of this thesis is to study and analyze the problem of applying the license system and criminal penalties in the production of beer for consumption, as well as to study and seek out other appropriate measures to control the production of beer for consumption in Thailand instead of using licenses and criminal penalties.According to the study, the main motivation for the introduction of licenses and criminal penalties for brewing for consumption is for government to collect more taxes. After an investigation on control patterns for the production of similar products such as tobacco for consumption, found that the production of tobacco for consumption does not regulate by a licensing system or criminal penalties. If producing tobacco for consumption without a license is not a crime. Therefore, the production of beer for consumption should not be regulated by a licensing and criminal penalties either. When examining the criteria for defining criminal offenses both in Thailand and abroad, it was found that defining brewing beer for consumption without a license as a criminal offense does not comply with the criminal offense criterion in any way. And when looking at the measures applicable to the production of beer for consumption abroad, it was found that even though the UK and Singapore have imposed criminal penalties on brewing beer for unlicensed consumption in the past, the country has now repealed those laws by allowing production without a license. Therefore, this thesis recommends the decriminalization of brewing beer for unlicensed consumption, allowing brewing for consumption without requiring a license. However, the researcher still believes that there should be some criteria to control the production of beer for consumption, which the researcher deems appropriate to allow persons aged 20 years and over be able to produce beer by prohibiting the sale of beer.